Molecular imaging in living subjects: seeing fundamental biological processes in a new light - Massoud, Tarik F.; Gambhir, Sanjiv S. (Genes & development, 2003)
The emergence of molecular imaging strategies is largely due to recent unprecedented advances in molecular and cell biology techniques, the use of transgenic animal models, availability of newer imaging drugs and probes that are highly specific, and successful development of small-animal imaging instrumentation. These factors, along with continued expansion of scientific horizons in the current postgenomic era, have been pivotal in the drive toward a new standard that allows linking established in vitro and cell culture experimental assays to imaging studies within living subjects. This now creates the possibility of achieving several important goals in biomedical research, namely, (1) to develop noninvasive in vivo imaging methods that reflect specific cellular and molecular processes, for example, gene expression, or more complex molecular interactions such as protein-protein interactions; (2) to monitor multiple molecular events near-simultaneously; (3) to follow trafficking and targeting of cells; (4) to optimize drug and gene therapy; (5) to image drug effects at a molecular and cellular level; (6) to assess disease progression at a molecular pathological level; and (7) to create the possibility of achieving all of the above goals of imaging in a rapid, reproducible, and quantitative manner, so as to be able to monitor time-dependent experimental, developmental, environmental, and therapeutic influences on gene products in the same animal or patient.